Pengelolaan Media Sosial Peace Generation Indonesia Dalam Mengampanyekan Nilai-Nilai Perdamaian - Aat Ruchiat Nugraha Nugraha (Jurnal Spektrum Komunikasi, 2020)
Technological advances are rapidly causing a change in a variety of ways, especially increasing the rapid use of the Internet that can utilize to abuse in the "hastening" situation of social peace. Through the use of social media in the form of Instagram conducted by Peace Generation Indonesia, we strive to know the development of issues and information that occur in the community and as well as the media campaign and dissemination of information messages. The research aims to determine the determination of the situation, goal setting, target audience, strategy, tactics, timelines, and budgets on social media of Peace Generation Indonesia. The method used in this study is qualitative descriptive based on the technique of data collection produced through observations, interviews, and literature studies. The results showed that the determination of the current situation in every area of life in the community is leading to the digital era and many social media accounts are "radical". As for the goal setting is to campaign the values of peace to the public with the target audience is the young urban generation for the strategy that is done by Peace generation Indonesia, namely community engagement, Agent of Peace (AoP), special event, and social media activation. The tactics used by Peace Generation Indonesia are by identifying problems, discussions, designing messages, and uploading content. The suggestion this research should conduct in-depth research that is more structured about setting target targets, interaction patterns with followers, schedules to upload content on Instagram social media and create budget activities. The research conclusion shows that the stages in Instagram's media management strategy are in line with Regina Luttrell's steps. The advice should be that Peace Generation Indonesia can more specialize in the message target of Perdaiaman campaign.